Oral fetus-in-fetu: A case report - Nurudeen Toyin Abdulraheem; Abdulrasheed A. Nasir; Lukman O. Abdur-Rahman; Oluwaseun R. Akanbi; Moses O. Olanrewaju; Muslimat A. Alada; Olanrewaju O. Oyedepo; Temitope Obasa; James O. Adeniran (Elsevier, 2015)
Fetus-in-fetu is a rare condition, less than 200 cases have been reported. Its embryopathogenesis is linked to a monozygotic, diamniotic parasitic twin. The presence of a calcified vertebral column and other body parts are key to the diagnosis, and differentiate it from a teratoma. We report a case of a neonate who was admitted immediately after delivery by Caesarian section following a prolonged obstructed labor caused by a huge mass projecting from the hard palate. The mass had identifiable malformed body parts but was anencephalic. Intraoperative findings were a short stalk and cleft of the soft palate. He had excision of the mass and did well post operatively. Persistent mouth breathing and difficult nasal cannulation lead to request for post operative magnetic resonance imaging which showed patent nostrils and absent residual mass. Prompt and skillful anesthesia and surgical intervention assisted in the survival of this patient.